Multiple Sclerosis Severity Score: Concept and applications. (April 2020) - Kister, Ilya; Kantarci, Orhun H
Severity score represents disease duration–adjusted mean rank of disability in multiple sclerosis (MS) patients from the reference population. This measure allows one to compare the relative rates of disease progression among patients, patient subgroups, and across epochs, which opens up new question of what accounts for the observed differences in severity, and can be used to assess correlation between disease severity and clinical, radiologic, immunologic, genetic, and environmental variables of interest. Severity score can also prove useful for developing prognostic tools in MS. This article discusses the diverse applications of severity score concept in MS research, and (re)introduces Herbert's proposal of severity-based MS classification in the context of variability of MS severity.